2018
DOI: 10.18820/2519593x/pie.v36i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the integration of modern technologies in the teaching of physical science in Lesotho

Abstract: The aim of the paper is to explore the knowledge base of high school physical science teachers, from selected high schools in Lesotho, regarding the integration of information and communication technologies (ICTs) into the curriculum. The new physical science curriculum in Lesotho requires the use of ICTs for teaching. The teachers' use of ICTs was explored through a questionnaire based on the technological pedagogical content knowledge model (TPACK). Data were analysed using the statistical analysis software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…It appears that the respondents printed the information obtained from the internet, hard disks, and CD ROMs to hand out to the learners and to back their teaching in the classroom. This is consistent with what [44] also found about Lesotho high school physical sciences teachers, that they irregularly used flash drives and printers to store information and make hard copies of the information for their learners. Therefore, results of this study confirmed that teachers use internet tools and computers mainly as sources of information used to update their subject knowledge and to better prepare for lessons, as established by [26], [32], [34], and [3].…”
Section: Discussion Of Key Findingssupporting
confidence: 89%
See 3 more Smart Citations
“…It appears that the respondents printed the information obtained from the internet, hard disks, and CD ROMs to hand out to the learners and to back their teaching in the classroom. This is consistent with what [44] also found about Lesotho high school physical sciences teachers, that they irregularly used flash drives and printers to store information and make hard copies of the information for their learners. Therefore, results of this study confirmed that teachers use internet tools and computers mainly as sources of information used to update their subject knowledge and to better prepare for lessons, as established by [26], [32], [34], and [3].…”
Section: Discussion Of Key Findingssupporting
confidence: 89%
“…Therefore, a larger sample, such as the one used in this study, was necessary to corroborate or extend the findings made by [43]. In another study, [44] found that Lesotho physical sciences teachers used flash drives and printers, though not so often, to store information and make hard copies of the material. Also, [45] established rare use of ICTs by teachers in physical sciences.…”
Section: Literature Reviewsupporting
confidence: 56%
See 2 more Smart Citations
“…One of the models used as a frame of reference is the Technological Pedagogical and Content Knowledge (TPACK) and we see the research of several authors reflected (Lai and Lin, 2018;Lisene and Jita, 2018;Yildirim and Sensoy, 2018;De Freitas and Spangenberg, 2019;Gómez, 2019;Li et al, 2019;Walan, 2020;Williams, 2020;Pamuk, 2022).…”
Section: Pedagogical Approaches In the Curricular Integration Of Educ...mentioning
confidence: 99%